Bilateral Neuropathy of Primary Sensory Neurons by the Chronic Compression of Multiple Unilateral DRGs - Ya-Bin Xie; Huan Zhao; Ying Wang; Kai Song; Ming Zhang; Fan-Cheng Meng; Yu-Jie Yang; Yang-Song He; Fang Kuang; Si-Wei You; Hao-Jun You; Hui Xu (Neural Plasticity)
To mimic multilevel nerve root compression and intervertebral foramina stenosis in human, we established a new animal model of the chronic compression of unilateral multiple lumbar DRGs (mCCD) in the rat. A higher occurrence of signs of spontaneous pain behaviors, such as wet-dog shaking and spontaneous hind paw shrinking behaviors, was firstly observed from day 1 onward. In the meantime, the unilateral mCCD rat exhibited significant bilateral hind paw mechanical and cold allodynia and hyperalgesia, as well as a thermal preference to 30°C plate between 30 and 35°C. The expression of activating transcription factor 3 (ATF3) was significantly increased in the ipsilateral and contralateral all-sized DRG neurons after the mCCD. And the expression of CGRP was significantly increased in the ipsilateral and contralateral large- and medium-sized DRG neurons. ATF3 and CGRP expressions correlated to evoked pain hypersensitivities such as mechanical and cold allodynia on postoperative day 1. The results suggested that bilateral neuropathy of primary sensory neurons might contribute to bilateral hypersensitivity in the mCCD rat.